2010
DOI: 10.3844/ajessp.2010.253.259
|View full text |Cite
|
Sign up to set email alerts
|

Advective Heat Transport in an Unconfined Aquifer Induced by the Field Injection of an Open-Loop Groundwater Heat Pump

Abstract: Problem statement:The increasing diffusion of low-enthalpy geothermal open-loop Groundwater Heat Pumps (GWHP) providing buildings air conditioning requires a careful assessment of the overall effects on groundwater system, especially in the urban areas. The impact on the groundwater temperature in the surrounding area of the re-injection well is directly linked to the aquifer properties. Physical processes affecting heat transport within an aquifer include advection (or convection) and hydrodynamic thermodispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The design of a tracer experiment is influenced by several factors such as the desired transport distance and testing duration, boundary conditions, and the type and density of the monitoring network (Ptak et al ). Also, earlier studies on heat‐tracer testing showed negative effects by heat conduction into zones with minimal flow, changes of viscosity and fluid density with temperature, and time‐varying boundary conditions (Lo Russo and Taddia ; Ma et al ; Giambastiani et al ). In our design, we consider the test criteria discussed in the following paragraphs to account for the aforementioned limitations and constraints.…”
Section: Conceptual Experimental Design and Instrumentationmentioning
confidence: 98%
“…The design of a tracer experiment is influenced by several factors such as the desired transport distance and testing duration, boundary conditions, and the type and density of the monitoring network (Ptak et al ). Also, earlier studies on heat‐tracer testing showed negative effects by heat conduction into zones with minimal flow, changes of viscosity and fluid density with temperature, and time‐varying boundary conditions (Lo Russo and Taddia ; Ma et al ; Giambastiani et al ). In our design, we consider the test criteria discussed in the following paragraphs to account for the aforementioned limitations and constraints.…”
Section: Conceptual Experimental Design and Instrumentationmentioning
confidence: 98%
“…However, due to possible viscosity and buoyancy effects, and their relationship with hydraulic conductivity (K), variation in temperature may modify the flow regime. Ma and Zheng (2010) concluded from numerical simulations that no substantial density effects occur when heating groundwater up by 15 • C. This same critical value is given by Russo and Taddia (2010), based on the recommendations by Schincariol and Schwartz (1990) that buoyancy effects only appear at density differences higher than 0.8 kg m −3 . However, this calculation is only valid if the groundwater temperature is close to 0 • C. By setting a starting temperature of 10 • C (which is more realistic for a shallow aquifer in a temperate climate), this critical density difference is already reached at a heating threshold of 8 • C. This value coincides with that by Ma et al (2012), who refined their previous findings using field experiments and numerical sensitivity analysis.…”
Section: Introductionmentioning
confidence: 85%
“…In all of our models, the ambient groundwater temperature is considered uniform and 10 • C. Viscosity and density effects increase with the temperature difference, T , in comparison to the ambient groundwater. These effects may distort the results of inversion, and thus a maximal difference of T = 8-15 • C has been suggested for thermal tracer testing (Doro et al, 2015;Ma and Zheng, 2010;Russo and Taddia, 2010). This severely constrains the applicability of heat as an active tracer, because it complicates interpretation of BTCs influenced by buoyancy forces.…”
Section: Role Of Injection Rate and Temperaturementioning
confidence: 99%
“…Tracers are commonly used to get insight into the hydraulic properties of the subsurface on the aquifer scale and to identify dominant transport routes. Among the many tracers used for aquifer characterization, heat is frequently injected as a thermal tracer in boreholes or wells (Anderson, 2005;Hermans et al, 2015;Rau et al, 2014;Saar, 2011). From measured breakthrough curves (BTCs), aquifer hetero-geneity and preferential flow paths are inferred (Bakker et al, 2015;Colombani et al, 2015;Klepikova et al, 2014;Leaf et al, 2012;Macfarlane et al, 2002;Vandenbohede et al, 2008;Wagner et al, 2014;Wildemeersch et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Travel times of traditional solute tracers are related to the hydraulic properties of aquifers, assuming that the main transport process is advection. This is the case given a sufficient ambient hydraulic or forced gradient during the experiment (Doro et al, 2015;Saar, 2011). One important difference of heat tracer transport over traditional tracers is that diffusion takes place not only in the pore fluid but in the rock matrix as well.…”
Section: Introductionmentioning
confidence: 99%